2018
DOI: 10.1016/s2214-109x(18)30329-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of providing near glasses on productivity among rural Indian tea workers with presbyopia (PROSPER): a randomised trial

Abstract: Clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 20 publications
4
101
0
2
Order By: Relevance
“…The study estimated that 65,000 more Optometrists, Ophthalmologists, Optical Dispensers and other eye care professionals would be required to provide these services and that a cost of approximately 25,000 million to set up and run would be returned 10 fold by providing much needed eye care services. Investing in eye care demonstrated a 22% productivity increase amongst tea plantation workers in India during a one-month period [8]. Investing in education for eye care has vast economic and health benefits for the community.…”
Section: No Optometristsmentioning
confidence: 99%
“…The study estimated that 65,000 more Optometrists, Ophthalmologists, Optical Dispensers and other eye care professionals would be required to provide these services and that a cost of approximately 25,000 million to set up and run would be returned 10 fold by providing much needed eye care services. Investing in eye care demonstrated a 22% productivity increase amongst tea plantation workers in India during a one-month period [8]. Investing in education for eye care has vast economic and health benefits for the community.…”
Section: No Optometristsmentioning
confidence: 99%
“…Despite this, most research on uncorrected refractive error has focused on impairment of distance vision. While presbyopia may once have been considered less problematic in rural LMIC settings due to lower literacy levels and life expectancy, recent studies have demonstrated a significant impact on quality of life and activities of daily living …”
Section: Introductionmentioning
confidence: 97%
“…The impact of presbyopia has become more pronounced in LMICs due to population aging and technological advancements . Chief among these is the growing reliance on smartphones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations